(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background: The stem cells have been reported in umbilical cord blood (UCB), the Wharton’s jelly, and in other perivascular mesenchymal areas within the cord. Two types of stem cells that have been identified in UCB are haemopoietic stem cells (HSCs), which are blood-forming, and mesenchymal stem cells (MSCs), which are supposedly pluripotent. Stem cells within the umbilical cord other than those in cord blood have been broadly termed umbilical cord matrix stem cells (UCMSCs). Objective: To analyze the histological and histomorphometric changes in early term and postdate human umbilical cord (HUC). Methods: Fifty samples of the HUC were collected from normal vaginal delivery and were divided into 25 UC as normal early term and 25 UC as normal postdate labor. The age of pregnant women was (18-30 years), whose mother had normal pregnancy and normal vaginal delivery. The UC were fixed in 10% formaldehyde for paraffin blocks preparation. Transverse sections were placed on standard glass slides for hematoxylin and eosin staining. Results: The mean±SD of the length in postdate UC was 58.76±4.72 cm, significantly more than in early term UC (46.12±2.65 cm, P